Accountability of Village Fund Allocation Management in Landungsari Village, DAU District, Malang Regency - Rizki Aprilia Dwi Susanti; Asih Widi Lestari (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2022)
This research aims to determine the accountability of Village Fund Allocation Management which includes: planning, implementation, supervision, and accountability. In this study the method used is a qualitative descriptive. The techniques used are observations of objects that are being traced and through interviews. The results in this study indicated that in the accountability of the management of village funds allocation in Landungsari village, it can be said to be transparent and accountable. The community plays an active role by participating in following development planning deliberations, as well as monitoring the use of village funds allocation in Landungsari directly supervised by a team of the Regional Government Agency.